Research on the Application of Pixel Art in Game Character Design - Tubagus Zufri; Dodi Hilman; Octavianus Frans (Bina Nusantara University, 2022)
This paper analyzes the development, basic design foundations, and design principles of character designs that are often found in today's games. This discussion relates to the ability of pixel styles to survive even though the design styles of the current digital art era are developing with diverse thoughts. Pixels are the basic elements of design that are capable of producing attractive design work. Looking at the current development of pixel styles, in the midst of the proliferation of 3D-based visual works, we can find that pixel styles still have an irreplaceable influence. Pixel-based designs are still being put into practice and applied in the form of games by more designers and artists